Between Promise and Constraints: Social Justice, Development, and Cohesion in Eritrea - Fikresus Amahazion (The Indonesian Institute of Science and Technology Research, 2025)
In recent years, social justice has become a central theme in global debates on equality, human rights, development, and political reform. Yet, much of this discourse remains shaped by Western frameworks, with limited scholarship engaging African perspectives on what constitutes a just society – and even less examining how African states themselves operationalize justice in pursuit of national development and peace. This paper contributes to filling that gap through a qualitative, multi-method study of Eritrea, where social justice is conceived not only as a moral imperative but also as a practical foundation for sustainable development, national cohesion, and long-term peace. The analysis traces the roots and manifestations of Eritrea’s approach, highlighting achievements in areas such as gender equality, social protection, and inclusive development, while also acknowledging persistent structural challenges. Eritrea’s pursuit of social justice is substantive, yet progress remains uneven and contingent on overcoming resource constraints, entrenched norms, and institutional limitations. Ultimately, Eritrea’s experience provides valuable insights for broader debates on social justice in low-income and post-conflict contexts, illustrating both the possibilities of state-led progress and the enduring obstacles to transformative change.